Pengaruh Kondisi Ekonomi Keluarga Terhadap Motivasi Belajar Siswa Dan Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Muhammad Fery Mustika; Khalid Ramdhani Faturrahman (ISLAMICA, 2017)
Departing from the writer's attention to see that the family economic conditions can affect student motivation for thestudy. Beside to the education, family economic conditions often become the factorthat influences student motivation in the study. While the motivation may make function as a driving force effort and accomplishment. This raises the problem for the author, of how the influence of family economic conditions towards student motivation on the study and student achievement, especially in the subject of Islamic Education Learning.This research aims to obtain empirical evidence on the effect of family economic conditions towards student motivation on study, the effect of the economic conditions of families on the learning achievement, the effect of economic conditions of the family towards student motivation on study and student achievement in SDN Babakanjati Education Development Center for Kindergarten/Elementary at District of Cilaku, Regency of Cianjur academic year 2014-2015. Research results are expected can contribute to expanding knowledge in the field of education, especially forIslamic Education Learning. Research results show that: (1) There is a positive and significant effect of family economic conditions (X) towards student motivation (Y1) with the coefficient of determination is 14.82%, (2) There is a positive and significant effect on students' motivation to student achievement with the coefficient of determination is 34.69%. (3) There is a positive and significant effect of family economic conditions (X) simultaneously against student motivation (Y1) and student achievement (Y2) with the coefficient of determination is 35.16%.